2020
DOI: 10.1055/a-1185-8762
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Effect of Macrolide Antibiotics Erythromycin, Clarithromycin, and Azithromycin on the ERG1 Gene Expression in H9c2 Cardiomyoblast Cells

Abstract: Macrolides are clinically well-established class of antibiotics. Macrolides induce cardiotoxicity by blocking ether-a-go-go–related gene (ERG) potassium channels in cardiac myocytes. The aim of this study was to compare the effects of erythromycin, clarithromycin and azithromycin on cell viability and expression of ERG1 gene in H9c2 cells. Cell viability and ERG1 gene expression of H9c2 cells in 3 different conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In addition to TIM-3, the activation of the PD-1/PD-L1 pathway in severe H1N1 influenza A infection has been demonstrated in tissue samples of the lower respiratory tract in pediatric patients and their dendritic and T cells as well [ 21 , 22 ]. PD-L1 expression levels are inversely related to the number of CD8 + T cells in these patients, and inhibition of this pathway improves the number and function of CD8 + T cells [ 23 ]. Rutigliano et al showed that decreased CD8 + T cells activity in influenza A virus infection in mice was associated with increased PD-1 expression [ 24 ].…”
Section: The Common Pattern Of Virus-induced Hyperinflammation Of Respiratory Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to TIM-3, the activation of the PD-1/PD-L1 pathway in severe H1N1 influenza A infection has been demonstrated in tissue samples of the lower respiratory tract in pediatric patients and their dendritic and T cells as well [ 21 , 22 ]. PD-L1 expression levels are inversely related to the number of CD8 + T cells in these patients, and inhibition of this pathway improves the number and function of CD8 + T cells [ 23 ]. Rutigliano et al showed that decreased CD8 + T cells activity in influenza A virus infection in mice was associated with increased PD-1 expression [ 24 ].…”
Section: The Common Pattern Of Virus-induced Hyperinflammation Of Respiratory Virusesmentioning
confidence: 99%
“…The antiviral activity is attributed to their binding to IFN-receptor and inducing STAT1/2, IRF7, IRF9, and production of ISGF3 as well [ 22 ]. Clarithromycin and Leucomycin are the examples of Macrolides, used against the influenza virus to increase IFN-α production [ 23 , 38 ]. Azithromycin is another macrolide that inhibits rhinoviruses via potentiating IFN-I signaling.…”
Section: Interventions Of Ifns and Their Agonists With Sars-cov-2 Infectionmentioning
confidence: 99%
“…At this time, only three cultivating cardiomyocyte cultures, murine HL-1, rat H9c2, and human AC-16 cell lines, are available. Despite the limitations, the H9c2 cell line is the most used in various experiments [31], including the study of antibiotics' cardiotoxicity [32].…”
Section: The Cardiotoxicity Of Compounds 1-6mentioning
confidence: 99%
“…[8][9] These chemical architectures are considered as ideal candidates for the pharmaceutical industries as many macrocycle-based antibiotics are clinically available such as azithromycin, erythromycin, vancomycin, daptomycin, bacitracin, spiramycin and rifampin. [10][11][12][13][14] They have been explored for their potential enzyme inhibition ability particularly for protein-protein interaction inhibitors, HIV protease inhibition, hepatitis C virus inhibition, kinase inhibition, anti-cancer and many others. [15][16][17][18] Besides, they are also being used in medicines as complexing agents in chelation therapy, in radionuclide therapy, energy storage molecules and as photochromes.…”
Section: Introductionmentioning
confidence: 99%